Exploring the Dynamics of Ecosystem Balance Research: A Bibliometric Analysis to Uncover Research Focus and Disciplinary Contributions - Dito Anurogo; Erwina Kartika Devi; Sarwono Sarwono; Lia Nurina (West Science Nature and Technology, 2023)
Ecosystem balance is a central concept in ecological research, with far-reaching implications for understanding and managing our natural world. This study employs bibliometric analysis to explore the dynamics of ecosystem balance research, uncover emerging trends, and identify the disciplinary contributions that shape this critical field. Leveraging an extensive dataset of scholarly publications, we examine the temporal evolution of research, geographic distribution, co-authorship networks, citation patterns, keyword co-occurrence, and disciplinary mapping. Our findings reveal a robust and multidisciplinary landscape, characterized by increasing global interest, collaborative research clusters, and influential publications. Key themes include carbon balance, ecosystem services, ecological equilibrium, and the interplay between human development and natural systems. This study provides valuable insights into the evolving ecosystem balance research domain, guiding future investigations and fostering interdisciplinary collaboration to address pressing environmental challenges.